LOCAL GOVERNMENT FINANCIAL REPORTS: UTILISATION OF INFORMATION TECHNOLOGY AND IMPLEMENTATION OF GOVERNMENT ACCOUNTING STANDARDS - Aris Biyantoro (JRAK, 2023)
Many local government financial reports are still not presenting data following the regulations and still show some irrelevancy. Therefore, this research aims at analyzing the impact of information technology (IT) and government accounting standards (GAS) implementation on the quality of local government financial reports (QLGFR). The sampling method used a sensory method. The data was collected by distributing questionnaires to 41 Regional Governments of Central Java Province. The results of the SEM-PLS test showed that IT did not affect the QLGFR. At the same time, implementing GAS positively affected the QLGFR. The results of this research had implications for the compliance of the Central Java Provincial Government with GAS which contained rules regarding the preparation of regional financial reports.